Cannabidiol's neuroprotective properties and potential treatment of traumatic brain injuries - Aychman, Mackenzie M.; Goldman, David L.; Kaplan, Joshua S. (Frontiers in Neurology, 2023)
Cannabidiol (CBD) has numerous pharmacological targets that initiate anti-inflammatory, antioxidative, and antiepileptic properties. These neuroprotective benefits have generated interest in CBD’s therapeutic potential against the secondary injury cascade from traumatic brain injury (TBI). There are currently no effective broad treatment strategies for combating the damaging mechanisms that follow the primary injury and lead to lasting neurological consequences or death. However, CBD’s effects on different neurotransmitter systems, the blood brain barrier, oxidative stress mechanisms, and the inflammatory response provides mechanistic support for CBD’s clinical utility in TBI. This review describes the cascades of damage caused by TBI and CBD’s neuroprotective mechanisms to counter them. We also present challenges in the clinical treatment of TBI and discuss important future clinical research directions for integrating CBD in treatment protocols. The mechanistic evidence provided by pre-clinical research shows great potential for CBD as a much-needed improvement in the clinical treatment of TBI. Upcoming clinical trials sponsored by major professional sport leagues are the first attempts to test the efficacy of CBD in head injury treatment protocols and highlight the need for further clinical research.